The Reading: A decisive experience - Meza Borja, Juan Aníbal (2018)
Reading is introduced as a vital experience, referring to experiences with the reading of intellectuals work such as J.P. Sartre, M. Proust, A. Manguel and M. Gutiérrez. The author talks about his reading experiences and those of his students. The value of reading is emphasized, defining it as an important experience for the formation of the individual. Books that provide strategies for profitable readings are reviewed.